2015
DOI: 10.14742/ajet.1992
|View full text |Cite
|
Sign up to set email alerts
|

Task selection, task switching and multitasking during computer-based independent study

Abstract: Detailed logs of students' computer use, during independent study sessions, were captured in an open-access computer laboratory. Each log consisted of a chronological sequence of tasks representing either the application or the Internet domain displayed in the workstation's active window. Each task was classified using a three-tier schema according to its likely context of use: The top-level categories being Academic, Communication, Information, Recreation and Applications. Students switched tasks frequently -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Conard and Marsh argued that their students used some advantageous multitasking strategies. In a similar vein, (Judd, 2015) investigated the tract records of computer logs during students' independent learning sessions. The study found that the students switched tasks frequently in averagely every 31 second across Academic, Communication, Information, Recreation and Applications tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Conard and Marsh argued that their students used some advantageous multitasking strategies. In a similar vein, (Judd, 2015) investigated the tract records of computer logs during students' independent learning sessions. The study found that the students switched tasks frequently in averagely every 31 second across Academic, Communication, Information, Recreation and Applications tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Although CA may be associated with individual traits, the role of student motivation and of the external environment in achieving such levels of immersion are also relevant. As multitasking and distractions posed by problematic internet habits (Bozoglan, Demirer, & Sahin, ; Judd, ) could interfere with the effective use of CDL technology, in their e‐learning programs, institutions should emphasize the importance of securing an environment that is conducive to CA, advising students on how to create such environment.…”
Section: Discussionmentioning
confidence: 99%
“…University students who have grown up in the digital world are used to the life that is always-on and constantly connected. On the university campus, multitasking with digital technologies has become the norm in formal (Hembrooke & Gay, 2003;Kraushaar & Novak, 2010) and informal learning settings (Judd, 2015;Rosen, Carrier, & Cheever, 2013). Although multitasking is not a new phenomenon, its frequency has increased markedly due to the pervasiveness and ubiquity of digital technologies (Wood & Zivcakova, 2015).…”
Section: Introductionmentioning
confidence: 99%